A randomized controlled trial comparing tapentadol with oxycodone in non-breastfeeding women post elective cesarean section: Tapentadol vs. oxycodone post elective cesarean section. (3rd June 2019) - Ffrench-O'Carroll, R.; Steinhaeuser, H.; Duff, S.; Close, J.; McNamara, J.; Ahmed, N.; Murray, M.; Rice, T.; Immanni, S.
Abstract: Background: Tapentadol may allow greater pain relief with reduced "opioid load" compared to oxycodone. Its use has not been studied in the obstetric population. The objective of this study was to compare the efficacy and side effect profile of tapentadol with oxycodone in patients who received spinal anesthesia for elective cesarean section. The trial was registered with EU Clinical Trials Register with CT number 2016-001621-33. Methods: This was a multicenter, randomized controlled trial. Randomized patients ( n = 68) received either 50 mg tapentadol or oxycodone 10 mg 12 hourly postoperatively. The primary endpoint was the sum of pain intensity difference over the first 48 hours of treatment (SPID48 ). Secondary outcomes included time to rescue medications, SPID36, total pain relief (TOTPAR) scores, patient satisfaction scores, sum of total pain relief and pain intensity difference (SPRID) scores, time to rescue medications and side effects experienced. An analysis of covariance model with baseline pain intensity score as a covariate was used for statistical analysis. Results: There was no significant difference in the primary endpoint of SPID48 with adjusted mean difference -11.45 (95% CI -35.35, 12.45) p = .34). Oxycodone showed significantly greater SPID36 scores compared to tapentadol with increased time to rescue medication. Side effects experienced were similar between groups. Conclusion: Tapentadol did not provide superior pain control or improved tolerability compared to oxycodone post cesarean section. Results should be interpreted however with consideration of administration of intrathecal opioids to all patients in this study and debate over the optimal dose of tapentadol for acute pain. Trial registration: EU Clinical Trials Register identifier: 2016-001621-33.